Al-Ghazali's Sufistic Economy Concept; From Homo Islamicus To Economic Progress - Havis Aravik; Achmad Irwan Hamzani; Nur Khasanah (At-Taradhi Jurnal Studi Ekonomi, 2023)
Islamic economics is present as a solution to the failure of capitalist and socialist economies in producing prosperity. Islamic economics is a new solution in answering various economic problems. For this reason, it is necessary to have the ability to access Islamic economic thought, especially from previous scholars to answer all existing problems. One such scholar is al-Ghazali. In Islamic economics, al-Ghazali offers a new perspective in the form of a Sufistic economic concept. This research is library research (library research) and is qualitative, which is sourced from primary and secondary data, and analyzed using content analysis both descriptively and inductively. The result is that Al-Ghazali no longer sees economic problems only in one field of knowledge, but is compared in various other fields of science to produce a comprehensive solution in which all human economic activity is part of worship to Allah Swt. For this reason, it must produce maslahah and falah in its activities. The state is obliged to play a role in ensuring that all of this is achieved by issuing various policies that help Muslims carry out their religious obligations as well as possible, including in economic matters and economic progress can only be achieved if justice, peace, and stability are fulfilled, in which the state plays an important role. inside it.